2020
DOI: 10.1136/thoraxjnl-2020-215128
|View full text |Cite
|
Sign up to set email alerts
|

Drive-through testing for SARS-CoV-2 in symptomatic health and social care workers and household members: an observational cohort study

Abstract: The requirement for health and social care workers to self-isolate when they or their household contacts develop symptoms consistent with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can lead to critical staff shortages in the context of a pandemic. In this report, we describe the implementation of a drive-through testing service in a single National Health Service region in Scotland. From 17 March 2020 to 11 April 2020, 1890 SARS-CoV-2 reverse transcription PCR assay (RT-PCR) tests w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Important strengths of the study including the large sample sample size, representation of multiple staff groups and the extensive SARS-CoV-2 testing of symptomatic healthcare workers in the region allowing correlation between antibody testing and prior SARS-CoV-2 RT-PCR. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important strengths of the study including the large sample sample size, representation of multiple staff groups and the extensive SARS-CoV-2 testing of symptomatic healthcare workers in the region allowing correlation between antibody testing and prior SARS-CoV-2 RT-PCR. 6…”
Section: Discussionmentioning
confidence: 99%
“…Measures taken to mitigate this increased risk include adequate personal protective equipment (PPE) 5 , infection prevention and control (IPC) procedures within healthcare environments and staff testing. Across the UK, testing for healthcare and other key workers with symptoms has been widely available since April 2020 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of household contacts in Bnei Brak, Israel [14], the secondary attack rate was 58.3% in adults aged 18-47y, 32.5% in children aged 5-17y, OR=0.35 (0.12,0.97) relative to adults, and 11.8% in children aged 0-4y, OR=0.09 (0.01,0.49) relative to adults. In a study of health and social care workers in Tayside, Scotland [15], the household secondary attack rates in pediatric contacts was 2.6%, while in adult contacts it was 19.5%, OR=9.13 (3.32,35.1). In a Chinese study [4], the attack rate among contacts of confirmed cases (not only household) was lower in children under the age of 15y compared to adults aged 15-64y (multivariable OR= 0.34 (0.24 to 0.49)).…”
Section: Introductionmentioning
confidence: 99%
“…Testing of asymptomatic HCWs is warranted especially in institutional outbreaks which can markedly reduce the staff work days lost due to self-isolation. 9 Outsidehospital or community was the source of infection as communicated by respondents which increased almost 15 times in second quadmester compared to first quadmester. This clearly points towards reduced relevance in risk stratification of HCWs based on workplace exposures.…”
Section: Discussionmentioning
confidence: 98%